A Pedagogical Integration of Teacher-Centered and Student-Centered Approaches in Imam Zarkasyi Method of Teaching Fiqh in Arabic within Modern Pesantren - Djamaluddin Perawironegoro; Nur Fitri Hidayanti (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The instruction of Fiqh in Pesantren commonly employs Arabic-language textbooks and learning resources. This context necessitates pedagogical methods that facilitate students’ comprehension of the material. However, teachers often encounter limitations in their methodological knowledge for delivering Fiqh in Arabic effectively. This study aims to describe and analyze Imam Zarkasyi’s method for teaching Fiqh in Arabic. Employing a qualitative approach and a literature-based design, data were collected through document analysis and processed using thematic content analysis, including stages of data collection, categorization, interpretation, and conclusion. The findings indicate that Imam Zarkasyi’s instructional method comprises five pedagogical stages: orientation, introduction, content delivery and integration, assessment, and closure. The approach emphasizes the integration of teacher-centered and student-centered strategies. Furthermore, effective Fiqh instruction requires teachers to possess pedagogical, professional, and personal competencies. The integration of methodological knowledge and teacher competencies enhances instructional effectiveness and supports students’ comprehension, thereby fostering more meaningful and efficient learning processes in the pesantren context.